Analysis of Nonverbal Communication in the Story of Hasanak the Vizier - Morteza Mohseni; Sayyed Esmail Jafari Petroudi (مطالعات زبانی و بلاغی)
The masters of literary works use verbal and nonverbal communication to present their thoughts and ideas more effectively. Although the poets and writers use literary language for aesthetic statement, they are not inattentive to nonverbal communication. Nonverbal communication is a collection of nonverbal stimulants in a communicational area created by both the source and this area and has potential message values for the source and receiver. This communication contains all unconscious body movements, appearances, voice specifications and the types of place and distance. Although it is not a certain medium for transmitting a message from one person to another, but it is more explicit than the oral language. This study attempted to analyze the samples of nonverbal communication, including physical appearance, gesture and movement, face and eye behavior, area and territoriality, tactility, environment and the nature of surroundings and period in the Hasanak the vizier’s story and endeavored to show how they made Bayhaqi’s language more effective. The results of the research show that the nonverbal message of phonetic behavior used for explaining the person’s emotions like protest, sadness, modesty, failure of communication, ridicule, lack of interest, etc. has the highest frequency and the nonverbal message of tactility, due to the description of court characters using it rarely, except for violence and contention, has the lowest frequency. In spite of mentioning the eight items of nonverbal communication in different sources of research, it seems that the Bayhaqi’s descriptions and preparation of surroundings in making a text narrative can be one of the nonverbal communication items not taken into consideration before.